Impact of Transformational Leadership on Organizational Commitment and Service Quality in Hospitality Sectors - Alkhaldi, Amal Hamoud; Abu Talib, Alyaa Afifah (Advances in Social Sciences Research Journal, 2025)
This study investigates the effect of transformational leadership (TFLD) on organizational commitment (OC) and service quality (SQ) in the hospitality sector. The study explores how transformational leadership influences employee commitment and how this commitment, in turn, affects service quality. The results reveal that TFLD significantly improves both OC and SQ, with OC acting as a mediator in the relationship between TFLD and SQ. The study contributes to a better understanding of leadership’s role in improving service quality within the hospitality industry, particularly in Saudi Arabia.